Representation of Alpha Woman in Korean Series (Roland barthes Semiotics Analysis on Pachinko Season 1 Series) - Afrina Nabila Azhari; Herlina Agustin; Samson CMS (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2025)
Korean dramas are not merely artistic works without meaning or purpose. They serve as a medium to depict social realities through storytelling and visual art. One of Korean dramas that reflects the social realities of Korea is Pachinko, set in the 1930s when patriarchal culture and the low status of women were still prevalent. The purpose of this study is to explore how the representation of alpha woman is depicted in Pachinko. The study adopts a qualitative approach, utilizing Roland Barthes’ semiotic analysis method to interpret the signs within the drama through three levels of analysis: denotation, connotation, and myth. The researcher selected three episodes from the eight-episode series (episodes 3, 4, and 5) for a detailed analysis of scenes referencing alpha woman characteristics. The findings of this research reveal various ways in which Pachinko portrays alpha woman. The study highlights the courage, independence, and resilience of woman characters. This research recommends that future Korean dramas continue to feature alpha women characters to inspire gender equality. Additionally, future studies could explore similar representations in different cultural contexts to provide comparative analyses, enriching the understanding of gender representation across cultures.